SISTEM REKAM MEDIS DAN PENDAFTARAN ONLINE BERBASIS WEB DAN ANDROID UNTUK MENINGKATKAN EFISIENSI KLINIK - Ghazalba, Zaedar; Anggara, Afwan (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The development of information technology has driven the digitalization of healthcare services, including registration and medical record systems in clinics. This research aims to design and implement an efficient online registration and medical record system based on web and Android mobile platforms. The system uses REST API technology to connect the online registration application with the clinic's secure database. The development method involves using the Laravel framework for the back-end and Kotlin for the mobile application. The results of this study indicate that the developed system can facilitate patient registration, reduce waiting times, and improve the efficiency of medical record management in clinics. Therefore, this system has the potential to enhance the quality of healthcare services in clinics that adopt it.